Incidence of spontaneous abortions and congenital anomalies in the vicinity of a uranium processing plant - Jírová, Jitka; Michalová, Zuzana; Beránek, Ladislav; Kotrbová, Květoslava; Zölzer, Friedo (Central European journal of public health, 2020)
OBJECTIVES: The exposure of embryos or foetuses to ionising radiation can cause serious detriments to health. Thus, an enhanced incidence of spontaneous abortions and congenital anomalies might be expected in the vicinity of a uranium processing plant. We analysed the situation in the vicinity of MAPE Mydlovary, a facility about 20 km from České Budějovice, South Bohemia, Czech Republic, which was in operation from 1963 to 1992. METHODS: No relevant data are available for the period of operation of the uranium processing plant. Statistical data have only been collected since 1994. As sanitation work in the area was initiated at around that time and has yet to be completed, we considered a study of possible prenatal effects in the vicinity of MAPE Mydlovary to still be of interest. Data were provided by the Institute of Health Information and Statistics of the Czech Republic for the years 1994-2013. RESULTS: We tested whether there are demonstrable, statistically significant differences between the microregions of the four closest villages (Mydlovary, Olešník, Zahájí, and Zliv), the District of České Budějovice, the South-Bohemian Region, and the Czech Republic. CONCLUSIONS: No increase was found in the incidence of spontaneous abortions and congenital anomalies in the vicinity of this former uranium processing plant compared to the surrounding District of České Budějovice, the South Bohemian Region, or the Czech Republic as a whole.
Keywords: embryo; Abortion, Spontaneous; Česká republika; radiation; Pregnancy; těhotenství; Uranium; incidence; vrozené vady; Residence Characteristics; Czech Republic; Power Plants; lidé; ženské pohlaví; elektrárny; Humans; Congenital Abnormalities; uranium mining; foetus; Female; uranium milling; samovolný potrat; Incidence; uran; charakteristiky bydlení; prenatal development